2020
DOI: 10.1007/s40620-020-00910-1
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3 in the prediction of contrast media induced acute kidney injury

Abstract: Background Dickkopf-3 (DKK3) has recently been discovered as a urinary biomarker for the prediction of acute kidney injury (AKI) after cardiac surgery. This finding needs to be confirmed for AKI in other clinical settings. The present study investigates whether DKK3 can predict contrast-induced AKI (CI-AKI). Methods We performed a prospective study in 490 patients undergoing coronary angiography. Primary endpoint was an increase in serum creatinine concentration ≥ 0.3 mg/dl within 72 h after the procedure. DK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…uDKK3 baseline levels were significantly higher in individuals that developed AKI. However, follow-up uDKK3 levels were not higher in individuals that developed AKI 23 . In a second study on 458 patients scheduled for cardiovascular procedures requiring contrast medium administration baseline uDKK3 to creatinine ratio was predictive for the development of AKI and persistent kidney dysfunction with thresholds of > 491 pg/mg and >322 pg/mg, respectively 24 .…”
Section: Dickkopf-related Proteinmentioning
confidence: 81%
“…uDKK3 baseline levels were significantly higher in individuals that developed AKI. However, follow-up uDKK3 levels were not higher in individuals that developed AKI 23 . In a second study on 458 patients scheduled for cardiovascular procedures requiring contrast medium administration baseline uDKK3 to creatinine ratio was predictive for the development of AKI and persistent kidney dysfunction with thresholds of > 491 pg/mg and >322 pg/mg, respectively 24 .…”
Section: Dickkopf-related Proteinmentioning
confidence: 81%
“…Urinary DKK-3 is a novel biomarker of acute kidney injury and CKD [ 14 , 15 , 19 ]. In particular, in non-dialytic CKD patients, urinary DKK-3 levels have been associated with CKD progression regardless of disease etiology [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…DKK-3, a member of the glycoprotein family (DKK1-4) (Gröne et al, 2017), is a recently discovered stress-induced tubular-derived renal biomarker for interstitial fibrosis (Federico et al, 2016;Fang et al, 2020;Seibert et al, 2021). It mainly promotes renal tubular epithelial cells producing fibrogenic molecules secreted by stress stimulation (Schunk et al, 2021a).…”
Section: Dickkopf-3mentioning
confidence: 99%
“…It mainly promotes renal tubular epithelial cells producing fibrogenic molecules secreted by stress stimulation (Schunk et al, 2021a). Expression of DKK-3 in the developing kidney would cease after kidney maturation and would reignite when the kidney tissue is damaged (Seibert et al, 2021). Lipphardt et al (2019) have found that DKK3 could significantly reduce the area percentage, total length, and bifurcation number of capillary structures in renal microvascular endothelial cells.…”
Section: Dickkopf-3mentioning
confidence: 99%